INTEGRATED LAND USE AND TRANSPORTATION ENGINEERING TRAINING PROGRAMME: FOSTERING TEAM WORK AMONG GRADUATE STUDENTS. - Raymond Akuh; Ming Zhong; Asif Raza (Universitas Diponegoro, 2021)
In recent years, the importance of integrated land use and transportation has received a lot of attention. Lack of knowledge on how land use and transportation affect each other during planning for urban development could have adverse effect on urban cities. Graduate students in Transportation Engineering are potential traffic, safety and urban transportation city planners. These graduate students therefore, need to have fundamental knowledge on how land use and transportation adversely affect the economy, environment, and social lives of people in a city. To achieve this, a three-month training programme on integrated land use and transportation was organized for 50 Transportation Engineering graduate students studying in various fields of Transportation Engineering in Wuhan University of Technology. To foster team work among the students, they were asked to form groups-these groups were formed as male only, female only and male-female. The student groups were assessed on three tasks (project undertaken, lab work and classroom presentations) after they have been taken through various land use and transportation modeling courses. The key finding of this study is that for all the three main assessment results, male-female groups achieved the highest average score and as well as the highest accuracy in their final project (travel demand model) task as compared to the other two gender groups. It is concluded that in order to promote innovation and creativity through diverse perspective, group work involving gender mix should be encouraged among students. The entire training programme has also successfully achieved its objective.